GENETIC PREDISPOSITION TO THE RISK OF POTENTIALLY MALIGNANT AND MALIGNANT HEAD AND NECK DISEASES, TP53, TLR2, DEFB1 GENE POLYMORPHISM - Guliuk, S.A.; Shnaider, S.A.; Dienha, O.V.; Yakimenko, D.O.; Rachynskyi, S.V.; Pryima, O.A.; Blazhkiv, N.O. (World of Medicine and Biology, 2025)
The study was devoted to the identifying associations between leukoplakia, head-and-neck carcinogenesis and single-nucleotide polymorphisms in three genes: the tumour-suppressor TP53 Arg72Pro (rs1042522), the cell-surface receptor TLR2 Arg753Gln (rs5743708) and the antimicrobial peptide gene DEFB1 G-20A (rs11362). The study involved 60 patients aged 25–55 years with leukoplakia (n=20), oncology (n=20) and control (n=20). Allelic variants of the genes were genotyped by allele-specific polymerase chain reaction. A genetic predisposition to diseases affecting the oral mucosa has been demonstrated for both the development of leukoplakia and the emergence of malignancies. A statistically significant association was observed between the rs1042522 TP53 Arg72Pro polymorphism, the rs11362 DEFB1 G-20A polymorphism and the risk of oral pathologies. Insight into these risk factors, coupled with early diagnostic screening, may enable individuals to adopt preventive measures that lower their probability of developing such conditions.
Keywords: DNA methylation; oral cancer; premalignant lesions; biomarkers; early diagnosis